2013
DOI: 10.1089/lap.2012.0291
|View full text |Cite
|
Sign up to set email alerts
|

The “T-Suspension Tape” for Liver and Gallbladder Retraction in Bariatric Surgery: Feasibility, Technique, and Initial Experience

Abstract: The "T-tape suspension" technique is simple, safe, and inexpensive and provides efficient retraction of the liver and gallbladder during bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Shibao et al 13 reported that the field of view was excellent when using the silicone disk, good when using the V-List and Nathanson's retractor, and only fair when using an alternative technique. These results are supported by Zachariah et al, 18 Goel et al, 11 and Schlager et al 12 The magnet-based retractor system, the Endograb, the VaroLift, and the retraction sponge all reported simple operation and a good field of view but with some limitations. The magnetic retractor has limited retraction capability as it only operates with tissue thickness of 1.5 cm or below.…”
Section: Ease Of Usesupporting
confidence: 52%
See 1 more Smart Citation
“…Shibao et al 13 reported that the field of view was excellent when using the silicone disk, good when using the V-List and Nathanson's retractor, and only fair when using an alternative technique. These results are supported by Zachariah et al, 18 Goel et al, 11 and Schlager et al 12 The magnet-based retractor system, the Endograb, the VaroLift, and the retraction sponge all reported simple operation and a good field of view but with some limitations. The magnetic retractor has limited retraction capability as it only operates with tissue thickness of 1.5 cm or below.…”
Section: Ease Of Usesupporting
confidence: 52%
“…12,13 The remaining papers analyzed the use and performance of specific devices in particular laparoscopic interventions. 12,[14][15][16][17][18][19][20][21][22] For the cost comparison a total of 13 papers from EMBASE and 62 from MEDLINE were retrieved. Only 15 fitted the criteria and were selected for further review.…”
Section: Quality and Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…13,14 Similarly, the T-suspension tape is another totally internal liver retraction technique using the Tevlon tail of a Jackson Pratt drain that is slung around the liver and sutured to the abdominal wall. Zachariah et al 15 reported a mean time of 4.5 minutes to place the retractor; there were no complications, and the technique provided good visualization and working space. Other authors have described methods where the liver is sutured directly to the abdominal wall using a monofilament suture.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the T-suspension tape is another internal liver retraction technique. 15 The tape was created using the Teflon (DuPont, Wilmington, DE) tail of a Jackson-Pratt drain secured to a Prolene (Ethicon, Blue Ash, OH) suture on a long straight needle. In this case, the liver is retracted by a transparenchymal passage of the needle, which is exteriorized and secured to the anterior abdominal wall.…”
Section: Discussionmentioning
confidence: 99%